Convergences between Social Exchange Theory and mediation of information and knowledge from the perspective of software developers a case study - Souza, Leonardo Pereira Pinheiro de [UNESP]; Santos Neto, Joao Arlindo dos; Moraes, Cassia Regina Bassan de [UNESP] (Univ Estadual Campinas - Sistema Bibliotecas, 2020)
Information and knowledge are essential for the survival of companies and people's daily lives. Furthermore, software is a fundamental element to manage this information. Programming professionals use information and organizational knowledge to develop their projects and work as a team. Information and knowledge represent power, and their sharing includes bargains, behaviors studied by the Social Exchange Theory. Sharing information effectively involves more than passing it on, it involves interference aiming the receiver's appropriation of it, for work execution, by means of information mediating subjects. This paper objective is to verify how information and knowledge are shared among software professionals, inferring how principles of Social Exchange Theory interfere or not in their mediation, highlighting the influence of egocentric and altruistic motivators, or motivation aimed at the group. As methodological procedures, a descriptive case study was carried out with software professionals, students of a public higher education institution, in Garca city, Sao Paulo state, as well as their administrative personnel, using questionnaires, interviews and analysis of the institution website. As a result, it was found that there is evidence of mediation of information and knowledge among those surveyed, since altruistic and egocentric motivations are dialectically reconciled in this mediation/sharing. The results are attributed possibly to internalized values during higher education period, as well to a psychologically positive work environment. It is concluded that there are convergences between the Social Exchange Theory and the mediation of information, both in theoretical and practical aspects, showing the possibility of mediation besides traditional informational equipment: libraries, archives and museums.
Keywords: Programming; Information mediators; Organizational knowledge